Managerial Competencies of the Construction Resident Necessary to Guidethe Crew in the Construction Front - Chávez Valencia, Luis Elías (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
The concept of competencies has regained special importance when talking about direction thus it has been evidencing the strong relationship with the competitiveness of the company by the resources and capabilities theory, and this is, if stronger profitability is being sought, it's a manager's duty to make the administration and management of the material structure, but also the social structure. In the construction industry, the difficulties in operating the material structure are the result of work skills, but the social structure requires managerial skills that are essential for the construction site manager since the construction front integrates social roles that are visible in the plural executive committees, which are a council of the manager, the foreman, the bricklayer, and the bricklayer's assistant, where the route-goal is established to optimize the production of work volumes and consequently profits, and it is there where the managers require knowledge and experience, but also leadership, communication, and negotiation, which are the skills of a manager that allow him to manage the board, make optimal decisions, and lead human talent to improve productivity with social development.
Keywords: Managerial competencies; Business competitiveness; Social roles; Construction site; Construction front.